1999
DOI: 10.1034/j.1399-3003.1999.13b15.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal nitric oxide concentration in paranasal sinus inflammatory diseases

Abstract: In normal upper airways, nitric oxide is generated by the paranasal sinus epithelium and then diffuses into the nasal cavities. This study examined whether or not nasal NO concentration is affected by paranasal sinus inflammatory diseases.The influence of obstruction (nasal polyposis) and/or inflammation (allergy or chronic sinusitis) of the paranasal sinuses on nasal NO concentration was evaluated in nasal allergic (n=7 patients) or nonallergic (n=20) polyposis, nonallergic chronic sinusitis (n=10) and Kartag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
100
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 26 publications
11
100
1
3
Order By: Relevance
“…We found an inverse correlation between nNO levels and CT scores in our study, and the nNO levels were the lowest in patients with severe sinus pathology as evidenced by complete sinus opacification on CT scans. This inverse correlation which is in accordance with studies by Ragab et al [27] and Arnal et al [31] suggests that the nNO levels may be of some value for evaluation of sinus pathology and to screen patients for sinus ostium patency as well as possible defects in mucociliary clearance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found an inverse correlation between nNO levels and CT scores in our study, and the nNO levels were the lowest in patients with severe sinus pathology as evidenced by complete sinus opacification on CT scans. This inverse correlation which is in accordance with studies by Ragab et al [27] and Arnal et al [31] suggests that the nNO levels may be of some value for evaluation of sinus pathology and to screen patients for sinus ostium patency as well as possible defects in mucociliary clearance.…”
Section: Discussionsupporting
confidence: 89%
“…Lindberg et al [25] made no distinction between chronic rhino-sinusitis with or without polyps and had nNO significantly lower compared to healthy controls. Whereas in a study by Arnal et al [31] nNO was not significantly lowered in the chronic sinusitis group, though in the nonallergic polyposis group it was significantly lowered and in both groups there was an inverse correlation of nNO levels with the extent of CT scan alterations. Arnal et al also reported that in the group with Kartagener's syndrome, the nNO concentration (13.1 ppb) was dramatically decreased compared with all other groups.…”
Section: Discussionmentioning
confidence: 71%
“…A great deal of NO is produced in the sinuses [5], but the contribution of sinus NO to that found in the nasal cavity is somewhat unclear. Some authors have claimed that sinus NO is the major source of nasal NO [5,20,21], while others believe the contribution from the sinuses is of minor importance [22]. In the present study, silent nasal NO output was between 5-50% lower immediately after repeated humming.…”
Section: Discussionsupporting
confidence: 42%
“…An important role of ostial patency in nNO concentration was suggested in a study by Bommarito et al (2008), who reported that levels of nNO in chronic rhinosinusitis with polyps were significantly lower than those in chronic rhinosinusitis without polyps. In nasal polyposis, the nNO concentration was inversely correlated with the number of occluded sinuses (Arnal et al 1999). Thus, measurement of nNO may be useful in the investigation of prolonged cough etiologies and could be a useful method for identifying sinusitis-induced cough.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous reports on nNO levels in sinusitis. In acute or chronic sinusitis, levels of nNO have been reported to be reduced, compared with healthy controls (Baraldi et al 1997;Lindberg et al 1997;Deja et al 2003); however, other studies have not confirmed this (Arnal et al 1999;Lundberg et al 2003;Wodehouse et al 2003). Treatment of sinusitis with antibiotics restored decreased nNO levels in children (Baraldi et al 1997) and adults (Degano et al 2005).…”
Section: Discussionmentioning
confidence: 99%